Penyusunan zonasi sederhana sebagai dasar pengembangan kawasan wisata di Padukuhan Jolosutro, Kalurahan Srimulyo, Kapanewon Piyungan, Kabupaten Bantul, Yogyakarta - Azis, Edza Agung Ardatama; Sugiarto, Eko (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
Padukuhan Jolosutro has three tourism potentials with different characteristics. Therefore, it is necessary to determine the zoning as the basis for the development of tourist areas in Padukuhan Jolosutro so that tourism development in this area can be more focused. The program implementation method used is the triangulation method. The result of the activity is a simple infographic about the zoning of tourism development in Padukuhan Jolosutro, namely the Pilgrimage Tourism Zone at the Sunan Geseng Tomb Complex, the Recreational Tourism Zone at Bukit Tinatar, and the Agro-tourism Zone in the community's farmland area. These three zones are expected to be used as the basis for the development of tourist areas in Padukuhan Jolosutro to be more focused by the theme of tourism as well as useful in making tour packages based on market segmentation.